Optimalisasi Media Digital dalam Pengelolaan Public Relations - Shania, Shania; Ismail, Fajri; Karoma, Karoma (Jurnal Inovatif Manajemen Pendidikan Islam, 2024)
This study aims to explore the optimization strategies of digital media in public relations (PR) management at Yayasan Perguruan Islam Adabiyah (YPI Adabiyah). The research methodology employed is a qualitative case study approach. The results indicate that YPI Adabiyah has successfully enhanced visibility, engagement, and community relations through well-planned digital strategies. Through social media, YPI Adabiyah actively addresses critical issues and provides engaging content, while their official website builds credibility by offering accurate and structured information. Interactive content production such as video tutorials and webinars supports learning and strengthens emotional connections with the audience. The use of analytic tools to measure digital PR campaign performance aids in more informed decision-making. Collaborations with influencers have proven effective in extending message reach and building a positive image for YPI Adabiyah. This study confirms that a comprehensive approach to leveraging digital media based on relevant communication and PR theories can assist educational institutions like YPI Adabiyah in remaining relevant and adaptable in an evolving digital era.